Art Music by Caribbean Composers: Guadeloupe - Gangelhoff, Christine; LeGrand, Cathleen (International Journal of Bahamian Studies, 2011)
Guadeloupe retains more than its colonial and cultural roots from France. It has been an Overseas Department of that country since 1946. Many of the art-musical styles of Guadeloupe are derived from the ballroom and couple-dance traditions of old, reinvented in a creole tradition: quadrilles, waltzes, biguines and mazurkas (Gerstin, 2007-2011). Two of the most influential and consumed popular music genres are gwoka and compas. The Festival Internationale Saint-Georges, held annually since 2010, was created to celebrate the music of Saint-Georges, to promote artists of colour and to perform classical music written by composers of African descent, though the main focus of the festival is classical music.